Interactions of the Mechanosensitive Channels with Extracellular Matrix, Integrins, and Cytoskeletal Network in Osmosensation - Jiao, Runsheng; Cui, Dan; Wang, Stephani C.; Li, Dongyang; Wang, Yu-Feng (Frontiers in Molecular Neuroscience, 2017)
Life is maintained in a sea water-like internal environment. The homeostasis of this environment is dependent on osmosensory system translation of hydromineral information into osmotic regulatory machinery at system, tissue, and cell levels. In the osmosensation, hydromineral information can be converted into cellular reactions through osmoreceptors, which changes thirst and drinking, secretion of antidiuretic vasopressin (VP), reabsorption of water and salt in the kidneys at systemic level as well as cellular metabolic activity and survival status at tissue level. The key feature of osmosensation is the activation of mechanoreceptors or mechanosensors, particularly transient receptor potential vallinoid (TRPV) and canonical (TRPC) family channels, which increases cytosolic Ca2+ levels and activation of osmosensory cells including VP neurons and triggers a series of secondary reactions. TRPV channels are sensitive to both hyperosmotic and hyposmotic stimuli while TRPC channels are more sensitive to hyposmotic challenge in neurons. The activation of TRP channels relies on changes in cell volume, membrane stretch, and cytoskeletal reorganization as well as hydration status of extracellular matrix, activity of integrins; different families of TRP channels could be activated differently in response to hyperosmotic and hyposmotic stimuli in different spatiotemporal orders, leading to differential reactions of osmosensory cells. Together, they constitute the osmosensory machinery. The activation of this osmoreceptor complex is also associated with the activity of other osmolarity-regulating organelles, such as water channel protein aquaporins, Na-K-2Cl cotransporters, volume-sensitive anion channels, sodium pump and purinergic receptors in addition to intercellular interactions, typically the astrocytic neuronal interaction. In this paper, we review our current understandings of the composition of osmoreceptors and the processes of osmosensation.